Edukasi Kepada Kader Posyandu Tentang Perawatan Bayi Baru Lahir Dengan Aplikasi “My Baby Care” - Hidayati, Laili Nur; Sukoco, Bekti; Purwanti, Endah (BADAN PENERBIT STIEPARI PRESS, 2025)
Neonates are newborns up to 28 days old who undergo organ system changes as a form of adaptation. The immaturity of these organ systems makes neonates vulnerable to health problems, which can lead to death. Causes of neonatal mortality include labor complications, premature birth, congenital abnormalities, sepsis, pneumonia, diarrhea, and tetanus. These are often related to the quality of delivery services, lack of optimal postnatal care in the first days of life, and limited community knowledge about proper newborn care.The aim of this community service program is to improve the knowledge and skills of health cadres, with outcome indicators including increased antenatal visits, complete basic immunization, improved newborn care services, and the absence of neonatal deaths. Activities include education on newborn care based on the “My Baby Care” application, demonstrations of app usage and newborn care procedures, and distribution of educational tools and materials. The “My Baby Care” application facilitates newborn care practices among health cadres and mothers. It contains videos and explanations on how to bathe and care for a baby’s skin, umbilical cord care, exclusive breastfeeding, proper breastfeeding techniques, and immunization. This application supports improved maternal and child health outcomes.